2009
DOI: 10.2337/db09-0591
|View full text |Cite
|
Sign up to set email alerts
|

Age, Obesity, and Sex Effects on Insulin Sensitivity and Skeletal Muscle Mitochondrial Function

Abstract: OBJECTIVEReductions in insulin sensitivity in conjunction with muscle mitochondrial dysfunction have been reported to occur in many conditions including aging. The objective was to determine whether insulin resistance and mitochondrial dysfunction are directly related to chronological age or are related to age-related changes in body composition.RESEARCH DESIGN AND METHODSTwelve young lean, 12 young obese, 12 elderly lean, and 12 elderly obese sedentary adults were studied. Insulin sensitivity was measured by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
187
1
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 252 publications
(217 citation statements)
references
References 51 publications
23
187
1
6
Order By: Relevance
“…The present study found a modest correlation between IR and expression of PGC1A, but no difference in any mitochondrial markers between PCOS women and non-PCOS women. Some studies have reported a similar dissociation between IR and mitochondrial function [19,43], which was highlighted by Nair et al [44] when comparing mitochondrial function of Asian-Indians with northern Europeans. In contrast with the present study, most studies of mitochondrial function and IR do not adequately control for physical activity, family history of type 2 diabetes, and body composition.…”
Section: Discussionmentioning
confidence: 82%
“…The present study found a modest correlation between IR and expression of PGC1A, but no difference in any mitochondrial markers between PCOS women and non-PCOS women. Some studies have reported a similar dissociation between IR and mitochondrial function [19,43], which was highlighted by Nair et al [44] when comparing mitochondrial function of Asian-Indians with northern Europeans. In contrast with the present study, most studies of mitochondrial function and IR do not adequately control for physical activity, family history of type 2 diabetes, and body composition.…”
Section: Discussionmentioning
confidence: 82%
“…During aging in normal subjects of either sex, a gradual increase in body weight is observed, which is associated with an unfavorable impact on metabolic profile and IR has been considered the main pathophysiological link between obesity and metabolic derangements (13,14). Moreover, in a normal population, the aging process is associated with a gradual increase in IR and b-cell decompensation, leading to DM development (15).…”
Section: Introductionmentioning
confidence: 99%
“…In young lean men born with low birth-weight, mitochondrial function by MRS and mitochondrial gene expression are intact, despite these subjects displaying several pre-diabetic characteristics [188]. Two groups have also reported measurement of in vitro ATP production capacity and respiratory charactersitics in mitochondria isolated from obese subjects and fail to see any difference compared to controls [189,190]. Studies in different ethnic groups have also provided data contrary to the mitochondrial dysfunction theory of insulin resistance.…”
Section: Human Studiesmentioning
confidence: 73%